PHYTOCHEMICAL SCREENING AND GC-MS PROFILING IN THE LEAVES OF SOLANUM INCANUM L - Sundar S; Pillai Y, Justin Koil (Asian Journal of Pharmaceutical and Clinical Research, 2015)
chromatograph-mass spectrometer (GC-MS) method. Methods: The phytochemicals present in the petroleum ether, methanol, ethanol extract of S. incanum L. leaves was investigated by using GC Shimadzu QP2010 system and GC interfaced to a MS equipped with Elite-1 fused silica capillary column. The compounds were separated by using helium as the carrier gas at a constant flow rate of 1.51 ml/minutes. Software adopted to handle mass spectra and chromatograms were GC-MS solution ver. 2.53. Results: Preliminary studies showed the presence of carbohydrates, coumarins, flavonoid, phenol, steroids, and phytosteroids. In the GC-MS analysis of petroleum ether, ethanol, and methanol extract of S. incanum L. reported the presence of 12 components. The major chemical constituents are docosahexaenoic acid, 1,2,3 propanetriyl ether (retention time [RT] 9.18), ergoline-8-carboxylic acid, 10-methoxy-6-methyl-methyl ester, (8a) (RT 10.63), ascorbic acid 2,6-dihexadecanoate (RT 11.9), propanoic acid, 2-(3-acetoxy-4,4, 14 trimethylandrost-8-en-17-yl) (RT 12.44). Conclusion: This type of GC-MS analysis is the first step towards understanding the nature of active principles in this plant. The isolation of individual bioactive components and their biological activity are necessary for future studies and help to find new drugs. Keywords: Gas chromatograph-mass spectrometer profiling, Phyto components, Solanum incanum L., Ascorbic acid 2,6-dihexadecanoate.